1997
DOI: 10.1175/1520-0493(1997)125<2662:tgohgt>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Genesis of Hurricane Guillermo: TEXMEX Analyses and a Modeling Study

Abstract: The transformation of a mesoscale convective system into Hurricane Guillermo was captured by aircraft and Doppler wind data during the Tropical Experiment in Mexico. The early phase of the system evolves in a way very similar to previously documented mesoscale convective systems, with a midlevel mesocyclone developing in the stratiform precipitation region. More unusually, the cyclone extends to low altitudes: A weak cyclone is discernable even in the 300-m altitude wind field. After another day of evolution, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
235
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 248 publications
(268 citation statements)
references
References 24 publications
23
235
1
Order By: Relevance
“…Such a diabatic heating profile leads to the formation of a mesoscale convective vortex (MCV) near the melting level roughly 36 hours into each simulation. At, or just prior to 2 days, a rapid collapse in low-level vorticity is seen in all cases due to downdraught-driven lowlevel divergence beneath the mid-level vortex (Bister and Emanuel, 1997, their Figure 13(a)). …”
Section: Kinematic Perspectivementioning
confidence: 97%
“…Such a diabatic heating profile leads to the formation of a mesoscale convective vortex (MCV) near the melting level roughly 36 hours into each simulation. At, or just prior to 2 days, a rapid collapse in low-level vorticity is seen in all cases due to downdraught-driven lowlevel divergence beneath the mid-level vortex (Bister and Emanuel, 1997, their Figure 13(a)). …”
Section: Kinematic Perspectivementioning
confidence: 97%
“…Following Bergeron (1950), recent work has hypothesized that a tropical depression vortex will begin to intensify only after the column-integrated relative humidity has become nearly saturated on the vortex scale (Rotunno and Emanuel, 1987;Emanuel, 1989;Bister and Emanuel, 1997;Raymond et al, 1998). The basis for this idea originates in observations showing that regions of deep cumulus convection have adjacent downdraughts that advect mid-tropospheric air possessing a minimum of moist entropy into the boundary layer (e.g.…”
Section: Relative Humiditymentioning
confidence: 99%
“…Dry air at middle levels can have a negative impact on convective activity by reducing the updraft buoyancy via entrainment and decreasing the precipitation efficiency within developing systems (Ruprecht and Gray 1974;Gray 1975;Bister and Emanuel 1997). As described by Moody et al (1999), the geostationary satellite water vapor imagery in cloud-free regions is sensitive to the relative humidity in the mid-to upper troposphere.…”
Section: Cloud-cleared Water Vapor Brightness Temperaturementioning
confidence: 99%
“…Palmé n (1948) discussed the link between TC formation and sea surface temperature (SST) and concluded that TCs typically form in regions where the SST exceeds 268C. It has been shown that dry air at midlevels, via its entrainment into convective updraft cores and subsequent reduction in both buoyancy and precipitation efficiency (Ruprecht and Gray 1974;Gray 1975;Bister and Emanuel 1997), can inhibit sustained deep convection and have a negative effect on TC formation. Furthermore, the explicit role of tropical convection in TC formation has received considerable attention.…”
Section: Introductionmentioning
confidence: 99%